Antibacterial Properties of Nanosilver PLLA Fibrous Membranes. (27th May 2009) - Li, Lin; Li, Yi; Li, Jiashen; Yao, Lei; Mak, Arthur F. T.; Ko, Frank; Qin, Ling
Abstract : Nanosilver has been studied as a valuable material for it strong antibacterial effects. In this study, we investigated the antibacterial properties of nano silver Poly-L-Lactic acid (Ag/PLLA) composite fibrous membranes. Ag/PLLA fibrous membranes were prepared with silver nanoparticles having weight ratio of silver nanoparticles to PLLA at 5% (w/w). In vitro antibacterial tests were performed using Escherichia coli (E. coli) and Staphylococcus aureus (Staph.) to determine the antibacterial capability of the Ag/PLLA fibrous membranes. As the results suggested, Ag/PLLA fibrous membranes showed strong antibacterial properties. Thus, Ag/PLLA fibrous membrane can be used as an antibacterial scaffold for tissue engineering.